(untitled) - Dunn, I.G. (Rome, 1989)
Its purpose is to assist in reaching correct decisions in discussions between various specialist during planning, design, implementation and management phases of major river basin development projects with fisheries potential.
Keywords: Fishery management,Aquaculture,Nuôi trồng thủy sản